2011
DOI: 10.1128/aem.05845-11
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia Species Are Major Inhabitants of White Lupin Cluster Roots

Abstract: The formation of cluster roots by plants represents a highly efficient strategy for acquisition of sparingly available phosphate. This particular root type is characterized by a densely branched structure and high exudation of organic acids and protons, which are likely to influence the resident bacterial community. Until now, the identity of the bacterial populations living in cluster roots has not been investigated. We applied cultivation-dependent and cultivation-independent methods to characterize the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 42 publications
(44 reference statements)
1
49
0
Order By: Relevance
“…Clones of band 1 (KF926419-KF926422) were phylogenetically similar to Burkholderia strains found in unpolluted and polluted sites (AF247491, DQ465451, FJ210816; Weisskopf et al, 2011;Friedrich et al, 2000), while clones of band 2 (KF926423-926425) were similar to strains of Burkholderia and Bradyrhizobium jicamae (JX010967, JN662515). Bacteria from the genus Burkholderia are typical soil inhabitants, and certain Burkholderia strains are resistant to hydrocarbons and are used in the bioremediation of oil-polluted sites (Bacosa et al, 2012;Weisskopf et al, 2011;Hamamura et al, 2008;Adetutu et al, 2013).…”
Section: Bacterial Species Identified After Sequencing Of Bands Obtaimentioning
confidence: 87%
See 1 more Smart Citation
“…Clones of band 1 (KF926419-KF926422) were phylogenetically similar to Burkholderia strains found in unpolluted and polluted sites (AF247491, DQ465451, FJ210816; Weisskopf et al, 2011;Friedrich et al, 2000), while clones of band 2 (KF926423-926425) were similar to strains of Burkholderia and Bradyrhizobium jicamae (JX010967, JN662515). Bacteria from the genus Burkholderia are typical soil inhabitants, and certain Burkholderia strains are resistant to hydrocarbons and are used in the bioremediation of oil-polluted sites (Bacosa et al, 2012;Weisskopf et al, 2011;Hamamura et al, 2008;Adetutu et al, 2013).…”
Section: Bacterial Species Identified After Sequencing Of Bands Obtaimentioning
confidence: 87%
“…Clones of band 1 (KF926419-KF926422) were phylogenetically similar to Burkholderia strains found in unpolluted and polluted sites (AF247491, DQ465451, FJ210816; Weisskopf et al, 2011;Friedrich et al, 2000), while clones of band 2 (KF926423-926425) were similar to strains of Burkholderia and Bradyrhizobium jicamae (JX010967, JN662515). Bacteria from the genus Burkholderia are typical soil inhabitants, and certain Burkholderia strains are resistant to hydrocarbons and are used in the bioremediation of oil-polluted sites (Bacosa et al, 2012;Weisskopf et al, 2011;Hamamura et al, 2008;Adetutu et al, 2013). Band 3 (KF926426-KF926429), which is sensitive to oily and radioactive components in the waste samples (not seen in contaminated H -and R-samples), was genetically similar to Hydrogenobacter hydrogenophilus (Z30242) uncultured Acidobacteria isolated from unpolluted grassland and forest soils (HQ598830, HQ599021; Naether et al, 2012) and an uncultured Chlorobiales bacterium found in a uranium mining waste pile (AJ295649, AJ536877; Selenska-Pobell, 2002).…”
Section: Bacterial Species Identified After Sequencing Of Bands Obtaimentioning
confidence: 87%
“…Several reports have indicated a strong association of species from the genus Burkholderia within the rhizosphere of plants (Compant et al, 2008;Oliveira et al, 2009), and have suggested that their presence could contribute to plant growth by liberating phosphates from soil organic compounds like phytic acid (Unno et al, 2005). Although some reports have also suggested that some strains of the genus Burkholderia possess a degrading ability of phytic acid (Hayatsu, 2013;Unno et al, 2005; Weisskopf et al, 2011), to date, there are no reports on the identification and biochemical characterization of phytases from this genus. This study represents the first biochemical characterization of a purified phytase from the genus Burkholderia and may contribute to a better understanding of this class of enzymes and their role in strain a13 metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…Cluster roots are considered particularly beneficial in P-depauperate soils (reviewed by Dinkelaker et al 1995;Neumann and Martinoia 2002;Lambers et al 2006). Cluster roots impact a small volume of soil by exuding protons, organic acids, secondary compounds and enzymes (Dinkelaker et al 1995;Shane and Lambers 2005;PaungfooLonhienne et al 2009), and, less well characterised, through interaction with microbes (Marschner et al 2002;Weisskopf et al 2011).…”
Section: Root Specialisations: Mycorrhizal Fungi N 2 Fixing Procaryomentioning
confidence: 99%